2019
DOI: 10.4330/wjc.v11.i2.57
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous devices for left atrial appendage occlusion: A contemporary review

Abstract: Patient with atrial fibrillation (AF) are at risk of developing stroke with the left atrial appendage (LAA) being the most common site for thrombus formation. If left untreated, AF is associated with 4 to 5 folds increase in the risk of ischemic stroke in all age groups. About 5% to 15% of AF patients have atrial thrombi on transesophageal echocardiography, and 91% of those thrombi are located in the LAA in patient with nonrheumatic AF. Although oral anticoagulants are the gold-standard treatment for stroke pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The WATCHMAN (Boston Scientific) is one such device and is the most commonly used worldwide. [2] [3] Here, we report the use of this new technology for the first time in the English-speaking Caribbean.…”
Section: Introductionmentioning
confidence: 94%
“…The WATCHMAN (Boston Scientific) is one such device and is the most commonly used worldwide. [2] [3] Here, we report the use of this new technology for the first time in the English-speaking Caribbean.…”
Section: Introductionmentioning
confidence: 94%
“…Comprehensive discussions of the efficacy, technical aspects, and regulatory status of the devices used for LAAO are available in several recent reviews. 17,18 Many, but not all, studies of these devices have systematically defined and reported rates and mechanisms of PDL (Table 1). 17 The incidence of PDL likely depends on the interaction between the LAAO device, anatomical characteristics of the LAA including variability in the morphology of the LAA ostium and body, and possibly tissue characteristics of the underlying atrial tissue (e.g., fibrotic remodeling) ( Figure 1).…”
Section: Incidence Of Pdl: Impact Of Diagnostic Modalitymentioning
confidence: 99%
“…LAA occlusion using the Watchman® device subsequently became a viable alternative to anticoagulation in patients with nonvalvular AF. Although several devices have been introduced for LAA occlusion since 2005 such as Atriclip®, Amplatzer Cardiac Plug®, Amplatzer Amulet® and Lariat® suture delivery device [13, 14], only the Watchman® (Boston Scientific) has received US FDA approval [15]. There are no current guidelines on the choice of short-term antithrombotic therapy following placement of the Watchman® device, the optimal time to discontinue anticoagulation following Watchman® device placement and the duration of follow-up imaging after device deployment.…”
Section: Introductionmentioning
confidence: 99%